Patient safety incident reporting systems and reporting practices in African healthcare organisations: a systematic review and meta-analysis - Andrea P Marshall; Georgia Tobiano; Gelana Fekadu; Rachel Muir; Michael J Ireland; Melaku Tadege Engidaw (BMJ Open Quality)
Background Patient safety incident reporting and learning systems are crucial for improving the safety and quality of healthcare. However, comprehensive evidence of their availability and use in African healthcare organisations is lacking. Therefore, this review aims to synthesise the existing literature on these systems and reporting practices within African healthcare organisations.Methods A systematic review and meta-analysis were conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Five electronic databases, including PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL) via EBSCOhost, Scopus, Web of Science and the Excerpta Medica Database (Embase), were searched to identify relevant records. Peer-reviewed articles and guidelines published in English were included in this review. Quality appraisal was performed using the Joanna Briggs Institute and Quality Assessment with Diverse Studies tool. A random effects model was used to compute the pooled prevalence using Stata V.17.0.Results A systematic search retrieved 9279 records, of which 39 (36 articles and 3 guidelines) were included in this review. Eight patient safety incident reporting and learning systems were identified, with compliance rates ranging from low (16%) to high (87%) based on the WHO criteria. The pooled prevalence of patient safety incident reporting practices was 48% (95% CI 40% to 56%). However, the studies exhibited high heterogeneity (I²=98.75%, p<0.001).Conclusion In African healthcare organisations, it is imperative to establish robust patient safety incident reporting and learning systems, as none of the existing systems fully meet WHO criteria. In addition, optimising the existing systems and encouraging healthcare professionals to improve reporting practices will enhance patient safety and outcomes.PROSPERO registration number CRD42023455168.